The Management of Debtor's Assets Declared Bankrupt by the Commercial Court - Jamillah; Maswandi; Bambang Lesmono (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2021)
This study deals with the management of debtor's assets declared bankrupt by the commercial court. The establishment of the Commercial Court is a differentiation step (specialization) of the general court made possible by Law no. 14 in 1970 Jo. UU no. 35 of 1999 Jo. UU no. 4 of 2004 concerning the Justice Law and the establishment of this Commercial Court is the separation of jurisdiction to examine bankruptcy applications from the District Court to the Court Commerce. The result shows that the arrangement and management of the assets of the Debtor after being declared bankrupt by the Commercial Court, the bankrupt Debtor does not have the right to manage and settle all of his assets, and the management and settlement of all the assets of the Debtor will be resolved by the Supervisory Judge, Curator and Creditors Committee, each of whom has different duties, the supervisory judge has the duty to supervise all actions taken by the curator.